Not just a matter of size: a hospital-level risk factor analysis of MRSA bacteraemia in Scotland. Issue 1 (December 2016) - Gibbons, Cheryl; van Bunnik, Bram; Blatchford, Oliver; Robertson, Chris; Porphyre, Thibaud; Imrie, Laura; Wilson, Julie; Fitzgerald, J.; Woolhouse, Mark; Chase-Topping, Margo
Abstract Background Worldwide, there is a wealth of literature examining patient-level risk factors for methicillin-resistantStaphylococcus aureus (MRSA) bacteraemia. At the hospital-level it is generally accepted that MRSA bacteraemia is more common in larger hospitals. In Scotland, size does not fully explain all the observed variation among hospitals. The aim of this study was to identify risk factors for the presence and rate of MRSA bacteraemia cases in Scottish mainland hospitals. Specific hypotheses regarding hospital size, type and connectivity were examined. Methods Data from 198 mainland Scottish hospitals (defined as having at least one inpatient per year) were analysed for financial year 2007-08 using logistic regression (Model 1: presence/absence of MRSA bacteraemia) and Poisson regression (Model 2: rate of MRSA bacteraemia). The significance of risk factors representing various measures of hospital size, type and connectivity were investigated. Results In Scotland, size was not the only significant risk factor identified for the presence and rate of MRSA bacteraemia. The probability of a hospital having at least one case of MRSA bacteraemia increased with hospital size only if the hospital exceeded a certain level of connectivity. Higher levels of MRSA bacteraemia were associated with the large, highly connected teaching hospitals with high ratios of patients to domestic staff. Conclusions A hospital's level of connectedness within a network may be a better measure of a hospital's risk of MRSA bacteraemia than size. This result could be used to identify high risk hospitals which would benefit from intensified infection control measures.